Intergenerational Occupational Mobility in Latin American Economies: An Empirical Approach - Ömer Tuğsal Doruk; Francesco Pastore; Hasan Bilgehan Yavuz (Global Labor Organization (GLO), 2020)
Identifying the determinants of intergenerational mobility is an important aim in the development literature. In this article, intergenerational transmission is examined for 6 neglected Latin American Economies (Brazil, Costa Rica, Ecuador, Mexico, Panama and Puerto Rico). We use a multinomial logit model of the determinants of choosing a white-collar job for a child of a father working in farming as compared to a child whose father had a blue- or a white-collar job. Our findings show that, in the studied countries, intergenerational occupation transmission is mainly linked to low skilled jobs. Our analysis confirms the low degree of social mobility typical of Latin America, contributing, in turn, to explain their low growth rate. Our findings help identifying specific target groups - talented young women coming from the agricultural sector - to develop in them soft skills while at primary or low secondary school and work-related skills while at the high secondary school or at the university.
Keywords: D60; I30; J24; J6; J62; 330; Intergenerational occupational mobility; Intergenerational mobility; Latin American countries